Barriers to Accessing Mental Health Services Among Emerging Adults with Co-occurring Substance Use and Mental Disorders in Coastal Kenya: A Qualitative Study - Soud Alli Tengah; Susan Chemtai Changorok; Josephine Musau Ndanu (Eastern African Journal of Humanities and Social Sciences)
A substantial proportion of adults who use drugs also experience co-occurring mental health disorders. Evidence from high-income countries highlights persistent challenges in accessing mental health services among this population. However, limited empirical data exist on the barriers faced by emerging adults (EAs), aged 18–29 years, in Kenya, particularly those with substance use disorders (SUD). This study aimed to explore the barriers to mental health service access among EAs who use substances in coastal Kenya. A cross-sectional qualitative design was employed across Mombasa, Kilifi, and Kwale counties. Data were collected through nine focus group discussions (FGDs) involving 88 participants. Interviews were guided by a semi-structured protocol, audio-recorded, transcribed, and analysed thematically using NVivo 11. Findings revealed a range of individual, community, and health system barriers. Key themes included perceived stigma, negative attitudes from healthcare workers, financial constraints related to medication and transportation, limited awareness of mental health services, and a preference for traditional and faith-based healers. Participants also cited a shortage of mental health professionals and treatment facilities. To address these barriers, the study recommends multilevel interventions including community-based mental health education to reduce stigma, integration of mental health services into primary care to improve accessibility, capacity-building of health professionals to enhance responsiveness, and collaboration with traditional and faith healers to strengthen referral pathways. These strategies should be tailored to the needs of emerging adults and coordinated by stakeholders such as the Ministry of Health, NACADA, faith-based leaders, and civil society organisations.